PERSPEKTIF ALKITAB TENTANG TANTANGAN DALAM PELAYANAN DAN RELEVANSINYA TERHADAP KESETIAAN HAMBA TUHAN MASA KINI - Enny Irawati (Jurnal Teologi Biblika, 2023)
Historical services often experience planning problems, even at times in a systematic way through and coordinating a group of parties related to the violations of God's servants. This research is intended to provide a new perspective so that God's servants remain faithful in the field of ministry even though they are experiencing various kinds of challenges. This study uses a qualitative research method by using inductive discovery of the Bible. The results of the research show that challenges in ministry have even occurred since the Old Testament era and continued until the ministry of the early church in the New Testament and it was found that God's servants and OT and NT remained focused on ministry and were proud to be God's ministers.